Analisis Gerak Permainan Ketapel:Pegangan dan Akurasi Tembakan - Rahesti, Nonik; Irawan, Fajar Awang (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2024)
Slingshot is a traditional game that has several techniques that must be known, some basic techniques in traditional slingshot games have not been fully understood by some activists. The purpose of this study was to analyze the biomechanics of grip and accuracy in traditional games. This research uses quantitative methods that are described in detail using descriptive analytics with a one shot case study design. The sample in this study consisted of 10 traditional game activists in Semarang Regency and had filled out inform consent as a willingness to participate in the study until completion. The data in this study used kinematic data obtained from the results of video analysis of shooting slingshot games using kinovea software version 0.9.5. The results of this research study found that the analysis of the handle and activists of the traditional slinghot game in Semarang Regency in the preparation phase had an average handle angle of 99.08 ± 5.995°, then in the release phase with an average handle angle of 99.66 ± 4, 977. The angle formed by the arm as a handle and the shoulder as a puller can affect the final result of the shot. The appropriate grip technique, namely the gangster grip, then the grip arm is straight, and forms an angle of approximately 90 degrees from the body's togok, is said to be effective because the technique will reduce at least vibrations in body movements which will result in increased shot accuracy.